A compliant teleoperation control method based on real-time dynamic impact force feedback and operator-sensing - Yiming Bin; Jinjun Duan; Lingyu Wang; Minhong Wan; Qiulan Huang; Hongtao Wu (Journal of Intelligent Manufacturing and Special Equipment)
Purpose – In the teleoperating process, the kinematically dissimilar mechanisms of the slave robots and the teleoperation devices will provide unplanned and discontinuous trajectories to the slave robots, which causes jitter on the slave robots that seriously affects the flexibility and accuracy of the teleoperation task without the operator-sensing. This paper aims to solve the above problem. Design/methodology/approach – This paper established the conventional mapping relationship between the teleoperation device and the robot, and found out the reasons of the impact of jitter on slave robots; the paper then implemented the bilateral force feedback of force/dimension at the mapping point, and iteratively solved the feedback force of each time according to its functional compensation relationship, thus forming the bilateral force feedback method of dynamic impact feedback and operator-sensing of the teleoperation system. Findings – The experimental result shows that the feedback force obtained would clearly make a feedback of the jitter states of the slave robot and enhance the operator-sensing ability, which enables the operators to avoid the jittering state of slave robots in real-time. Originality/value – We propose a compliant teleoperation control method based on dynamic impact force feedback and operator-sensing. The effectiveness of the method has been verified in experimental validation, ensuring the compliant motion of the slave robot in various scenarios, which makes the teleoperated robots capable to be used in more high accuracy required tasks with a stable status.